The effects of substrate porosity, mechanical substrate properties and loading conditions on the attachment performance of the Mediterranean medicinal leech (Hirudo verbana). Issue 188 (23rd March 2022) - Kampowski, Tim; Schuler, Benedikt; Speck, Thomas; Poppinga, Simon
Abstract : The ectoparasitic lifestyle of the Mediterranean medicinal leech ( Hirudo verbana ) requires reliable functioning of its attachment organs (i.e. anterior and posterior suction discs) on multiple habitat- and host-specific surfaces under both normal and shear stresses. In addition to some intrinsic properties of the attachment devices, however, only a few extrinsic factors (e.g. substrate roughness and porosity) have been considered in previous studies on leech suckers. Using centrifugal force experiments, we analysed the attachment performance of H. verbana under different types of loading on artificial substrates differing in porosity and their mechanical properties. Whereas the substrate porosity significantly influenced leech attachment under normal and shear loading, the different mechanical properties did not noticeably affect attachment within the considered parameter limits. Furthermore, suction was confirmed to be the primary attachment mechanism independent of the prevailing loading condition. The question of whether the suction cups of H. verbana are adapted to a specific loading condition could not be answered. In any case, our results again highlight the high functional resilience of leech suckers guaranteeing a successful ectoparasitic lifestyle.